2013
DOI: 10.1371/journal.pone.0057472
|View full text |Cite
|
Sign up to set email alerts
|

Gene Knockout Study Reveals That Cytosolic Ascorbate Peroxidase 2(OsAPX2) Plays a Critical Role in Growth and Reproduction in Rice under Drought, Salt and Cold Stresses

Abstract: Plant ascorbate peroxidases (APXs), enzymes catalyzing the dismutation of H2O2 into H2O and O2, play an important role in reactive oxygen species homeostasis in plants. The rice genome has eight OsAPXs, but their physiological functions remain to be determined. In this report, we studied the function of OsAPX2 gene using a T-DNA knockout mutant under the treatment of drought, salt and cold stresses. The Osapx2 knockout mutant was isolated by a genetic screening of a rice T-DNA insertion library under 20% PEG-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(116 citation statements)
references
References 37 publications
3
112
0
1
Order By: Relevance
“…However, CAT activity can be inhibited by herbicides induced by ROS like methyl-viologen/paraquat (PQ) and 3-aminotriazole (AT) (Gechev et al, 2008;Qureshi et al, 2011). The rice APX plays an important role in development especially at seedling and reproductive stage by scavenging H2O2 under drought and some of the other abiotic stress (Zhang et al, 2013).…”
Section: Antioxidant Defense System and Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CAT activity can be inhibited by herbicides induced by ROS like methyl-viologen/paraquat (PQ) and 3-aminotriazole (AT) (Gechev et al, 2008;Qureshi et al, 2011). The rice APX plays an important role in development especially at seedling and reproductive stage by scavenging H2O2 under drought and some of the other abiotic stress (Zhang et al, 2013).…”
Section: Antioxidant Defense System and Rosmentioning
confidence: 99%
“…Rice genome contains eight APX genes that translate different isoforms of APX enzyme. Out of these genes, OsAPX2, a member of cytosolic APX genes (Teixeira et al, 2006) and key element of reactive oxygen network in rice genome, plays role in defense against oxidative injury caused by drought stress in rice seedlings (Zhang et al, 2013). It has been reported that APX8 andAPX3 genes were responsible for drought tolerance in IR64 and Nagina 22 rice genotype, respectively (Prakash et al, 2016).…”
Section: H2o2mentioning
confidence: 99%
“…79,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] Although chloroplasts, mitochondria, and peroxisomes are the significant sources of ROS, Arabidopsis knockout mutants lacking organellar APX isoenzymes showed very weak phenotypes against oxidative stress. 79,[102][103][104]107) cAPX is known to be more important for stress tolerance than other APX isoenzymes even though the cytosol is not a significant source of ROS.…”
Section: Physiological Rolesmentioning
confidence: 99%
“…3) It has been reported that cAPX expression is induced by various stresses, including heat, [4][5][6][7][8] strong light, 6,9,10) cold, 7,11,12) salinity, 7,12) and drought. 4,12,13) Overexpression of cAPX conferred tolerance of salinity, 12,14,15) drought, 12) and cold 12,16) on plants.…”
mentioning
confidence: 99%
“…4,12,13) Overexpression of cAPX conferred tolerance of salinity, 12,14,15) drought, 12) and cold 12,16) on plants. Furthermore, cAPX deficient mutants and transgenic plants have been reported to exhibit suppressed growth and development 6,12,13) and reduced stress tolerance, 12,17) although cAPX deficiency sometimes conferred enhanced tolerance of environmental stresses, probably by activating redundant mechanisms. 13,17,18) This indicates that cAPX plays important roles in plant growth and stress defense.…”
mentioning
confidence: 99%